Scaling behavior of iron in capacitive deionization (CDI) system. (15th March 2020) - Wang, Tianyu; Zhang, Changyong; Bai, Langming; Xie, Binghan; Gan, Zhendong; Xing, Jiajian; Li, Guibai; Liang, Heng
Abstract: This study investigated the fouling and scaling behaviors in a capacitive deionization (CDI) system in the presence of iron and natural organic matter (NOM). It was found that the salt adsorption capacity (SAC) significantly decreased when treating Fe-containing brackish water, with higher Fe concentrations leading to severer SAC reduction. Raman spectroscopy, X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD) analysis demonstrated that Fe2 O3 appeared to be the predominant foulant attached on the electrode surface, which was difficult to be removed via backwashing, indicating the irreversible property of the foulant. Further characterizations (e.g., N2 sorption-desorption isotherms, electrochemical impedance spectroscopy and cyclic voltammetry) revealed that the CDI electrodes suffered from obvious deterioration such as specific surface area loss, resistance increase and capacitance decline with the occurrence of Fe scaling. While the presence of NOM alleviated the Fe scaling through NOM-Fe complexing effects, NOM itself was found to have negative impacts on CDI desalination performance due to their strong interactions with the carbon electrodes. Graphical abstract: Image 1 Highlights: Iron scaling caused a significant decrease in desalination performances of CDI. Fe2 O3 was the predominant component of iron scale. CDI fouled suffered from resistance increasing and capacitance losing. NOM reduced precipitation of Fe on electrodes due to coagulation effect.